Edukasi Pencegahan Rabies Berbasis Klinik Hewan sebagai Penguatan Program Kesehatan Masyarakat Veteriner - Yulian Syah, Nanda; Zamzami, Rumi Sahara; Ferdian, Riyan (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
Rabies is a zoonotic disease that poses a significant threat to public health and can be fatal. A lack of public understanding and education about rabies has led to an increasing risk and prevalence of the disease each year. Using animal clinics as a platform for public education is one strategy to help control this disease. The objective of this community service project was to provide information and facilitate discussions with the public about the dangers, impacts, and management of rabies prevention. The method used was a Community-Based Research (CBR) approach, and data from pre-test and post-test assessments were analyzed using a paired t-test. The results of the project showed an increase in understanding among participants (pet owners who visited the animal clinic). The participants' post-test scores were higher than their pre-test scores. The average pre-test score was 30.7%, while the average post-test score was 68.9%. A statistical paired t-test was conducted on these results, yielding a t-value of -19.18, which indicates a significant difference between the pre-test and post-test scores (p < 0.05). This suggests that the animal clinic based rabies education was effective in increasing the knowledge and understanding of the community, especially among pet owners